Compliance Analysis of Fiberglass Boat Construction by CV. Roni Marine with BKI Standards - Yopi Novita; Asyifa Hidayanti; Vita Rumanti Kurniawati (International Journal of Marine Engineering Innovation and Research, 2026)
Technological developments have encouraged the shift in the main material from wood to Fiber Reinforced Plastic (FRP) because of its light weight, noncorrosive, lower price, and simple production process. However, traditional FRP boat production in Indonesia generally has not implemented the construction standards set by the Indonesian Classification Bureau (BKI), including those of CV. Roni Marine boat production. This study aims to describe the construction of FRP boats produced by CV. Roni Marine and assess its compliance with BKI standards. The research was conducted through direct observation at CV. Roni Marine, measuring the dimensions of the 9.5 m FRP boat construction, and literature studies of the BKI standard documents. The main components of boat construction analyzed include the boat's skin, keel, frames, longitudinal stiffeners, and deck beams. The results showed that the CV. Roni Marine uses a combination of transverse and longitudinal construction systems with laminated materials, including CSM300 and WR600 fibers. The thickness of the hull laminate is 2.13 mm. The spacing between frames is 580 mm, length of the longitudinal stiffeners is 8,700 mm, the width of the keel lamination is 60 mm, and the spacing between the deck beams is 2,900 mm. The results show that 100% of the boat construction does not comply with BKI standards